COUNSELLING – VARIOUS WAYS OF FINDING SOLUTIONS IN DIFFICULT SITUATIONS - Monika Wojtkowiak (Rozprawy Społeczne)
The article presents an attempt to indicate new forms of helping actions within advisory service. The emphasis is on the dialogic advisory service and its use in contemporary actions supporting the individual in challenging situations. The needs and restrictions of individuals looking for help are highlighted; however, new forms of work, which may be the answer to the rising need for help in various matters (strengthening the individual, solving conflicts, searching for new resources) have been indicated.